Use of the Discussion Method in Learning Maharoh Qiroah Lil Mutaqoddim at PBA UMSIDA - Ana Dewi, Siti; Fitriani, Laily (Tatsqifiy: Jurnal Pendidikan Bahasa Arab, 2024)
Nowadays the process of learning maharoh qiroah is too observant. Therefore, a lecturer must be able to look for methods that can make learning maharoh qiroah more active. This research aims to describe the maharoh qiro’ah learning process using the discussion method in the UMSIDA semester 3 PBA class. In this research, researchers used a qualitative approach with a case study strategy. Data collection techniques in this research are observation and documentation. The technique applied in analyzing data is interactive qualitative analysis using the Mikes and Huberman model. The results of this research in the learning process of lecturers use the group discussion method. Where the lecturer divides into several small groups. The discussion method in the maharoh qiro’ah learning process is used to make it easier for students to translate the reading texts contained in the qiro’ah genealogy ta’limiyyah mustawa 3 book. This is in line with one of the objectives of maharoh qiroa’ah learning, namely Understanding the text qira’ah perfectly and in detail.